Isolation and Cytotoxic Effect of Anthraquinones from Morinda umbellata - Chiou, Chun-Tang; Hsu, Ruie-Yu; Lin, Lie-Chwen (Planta Medica, 2014)
Four new anthraquinones, 1,6-dihydroxy-2-methoxymethylanthraquinone (1), 6-hydroxy-7-methoxy-2-methoxymethylanthraquinone (3), 3,6-dihydroxy-7-methoxy-2-methylanthraquinone (4), and 6-hydroxy-2-methoxymethylanthraquinone (8), together with 12 known anthraquinones and 6 other known compounds, were isolated from the EtOAc extract of Morinda umbellata. Among the isolated compounds, 1, rubiadin (14), and, 3-hydroxy-2-hydroxymethylanthraquinone (16) exhibited significant cytotoxicities against HepG2 cells, with GI50 values of 4.4, 3.6, and 4.8 µM, respectively.
Keywords: Morinda umbellate; Rubiaceae; 1,6-dihydroxy-2-methoxymethyl-anthraquinone; 6-hydroxy-7-methoxy-2-methoxymethylanthraquinone; 3,6-dihydroxy-7-methoxy-2-methylanthraquinone; 6-hydroxy-2-methoxymethylanthraquinone; cytotoxicity